Timing of the Sense of Volition in Patients With Schizophrenia - Pirio Richardson, Sarah; Triggiani, Antonio I.; Matsuhashi, Masao; Voon, Valerie; Peckham, Elizabeth; Nahab, Fatta; Mari, Zoltan; Hallett, Mark (Frontiers in Neuroscience, 2020)
Schizophrenic patients often do not have the sense that they direct their own movements or author their own thoughts (passivity phenomena). As willing must precede movement to be causal and thus generate the sense of agency, it is possible that the timing between the senses of willing and movement is shortened in schizophrenia. We tested the subjective perception of this time interval in patients with schizophrenia using a method based on Libet’s paradigm, in which subjects specify a time W - the time of willing a movement - and a time M - the time that movement occurred. Patients with schizophrenia and healthy volunteers made voluntary movements at times of their own choice while looking at a fast-rotating clock on a computer screen and reported when their movements were willed and made. We recorded surface electromyography to determine the time of actual movement, and electroencephalography to record brain potentials associated with movement. Results showed a significantly reduced interval between the reported M and W in patients with respect to the healthy volunteers (p<0.05). Specifically, patients did not report a significant difference in the timing of W at 19 ms prior to movement onset and M at 7.4 ms prior to movement onset (p>0.05), while the control group experienced a time W at 100 ms prior to movement onset and this differed significantly from their time M at 19 ms prior to movement onset (p<0.01). These results suggest that patients with schizophrenia do have an altered timing of awareness of action - or an impaired judgment of the sequence of events - and that this might be etiologic in the development of the abnormal sense of agency.